2020
DOI: 10.1007/s10549-020-05741-z
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of communication interventions to help healthcare professionals discuss genetic testing for breast cancer

Abstract: Purpose This systematic review examined educational training interventions for healthcare professionals (HCPs) discussing genetic testing and risk for hereditary breast cancer. There was a particular focus on the presence, and content, of communication elements within these packages. Methods Searches were run via CINAHL, EMBASE, PUBMED, and PsychInfo in February 2019 to identify training interventions available to HCPs with reference to communication skills. Studies were assessed for quality, with relevant int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Several modules have been developed to train healthcare professionals in how to provide counseling regarding hereditary diseases [ 40 , 41 ]. Many of these have been developed for NGHCPs and they mainly focus on attitudes about counseling, communication skills and knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Several modules have been developed to train healthcare professionals in how to provide counseling regarding hereditary diseases [ 40 , 41 ]. Many of these have been developed for NGHCPs and they mainly focus on attitudes about counseling, communication skills and knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Educational programmes designed to improve communication may fail to change behaviours effectively if the methods used or the contents of them are inappropriate. Our systematic review conducted prior to the development of TRUSTING revealed that there were few publications evaluating interventions explicitly designed to help HCPs discussing hereditary breast cancer risk and testing and that most failed to operationalise the skills that were included, outcome measures or analysis [12]. More recently, an influential report on the guidelines for genomics education has been published which might assist future programme developers [25].…”
Section: Discussionmentioning
confidence: 99%
“…During Phase 1, we conducted a systematic review of all relevant communication skills training programmes dealing with the genetic testing of high-risk breast cancer patients. We determined their content, methods of delivery, how outcomes had been measured and how successful programmes had been [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…Existing reviews mostly examine cancer genetics5–10 with the most recent review that focused on general clinical genetics published in 2016 11. Existing reviews have found that GPs experienced a lack of knowledge and confidence in basic genetics and risk assessments in the provision of clinical genetic services 5 7 8 12 13.…”
Section: Introductionmentioning
confidence: 99%
“…However, little is known about whether existing educational initiatives and clinical interventions has changed GPs’ experience and attitudes towards the adoption of clinical genetics. Also, most reviews focusing on primary care mostly included specialists such as oncologists, genetic counsellors, paediatricians and allied health professionals in their study population 5–8 10 12 13. While alike, specialists would yield different experience as practice styles are heterogeneous 14.…”
Section: Introductionmentioning
confidence: 99%